CO-PRODUCING SUSTAINABLE SOLUTIONS IN INDIGENOUS COMMUNITIES THROUGH SCIENTIFIC TOURISM: A CASE STUDY ON BADUY VILLAGE IN BANTEN - Budiatiningsih, Mahmudah (Jurnal Internasional Riset Bisnis Pariwisata, 2024)
Sustainable development is a common agenda of various world countries including Indonesia. This development is applied in various sectors, one of which is tourism, known as the sustainable tourism development approach. This concept supports tourism activities that pay attention to natural, cultural, and environmental aspects in their management. One form of alternative tourism that can support sustainability is scientific tourism. This form of tourism is usually carried out by researchers who travel in the context of research or data collection. One of the locations that has become the destination of scientific tourism is Baduy Village. Various studies were conducted with respondents in the form of the Baduy tribe community, both with a co-production approach and through an extractive approach. The high intensity of research conducted for various interests, while the benefits of the research are not necessarily felt by the Baduy community. It is feared that it will have a negative impact on the Baduy community, especially in the socio-cultural aspect. In anticipation of this, efforts to control tourism activities need to be made. One of the ways that can be taken is the provision of boundary parties that ensure that the interaction between the community and tourists is safe, which can be in the form of tour guides and the formation of boundary organizations. The role of boundary parties is to provide access and provide education services by adjusting to the needs of researchers.